Health risks to the world's young - Leunig, Sunny; Stavridis, Katrina; McLead, Matt (Video Education Australasia, 2011)
"The 'Convention on the Human Rights of Children', which asserts the fundamental right of children to be free from discrimination and disadvantage, is the single most ratified human rights treaty in history. Yet to this day there are still many factors that pose a risk to the health of the world's young. This program examines the most prominent of these risks: early pregnancy and childbirth, HIV/AIDs, malnutrition, mental illness, smoking, alcohol, and violence. The information in this program is supported by insight from experts in each field, and delivered with a non-alarmist approach that focuses on the facts"--Container.